Site-specific protein and cell surface engineering using asparaginyl peptide ligases - Zhang, DingPeng (Nanyang Technological University, 2022)
Peptidyl Asx-specific ligases (PALs) effect peptide ligation by catalyzing transpeptidation reactions at Asn/Asp-peptide bonds. Owing to their mild aqueous reaction conditions and high efficiency, PALs have emerged as powerful biotechnological tools for protein manipulation in recent years. PALs belong to the family of enzymes called asparaginyl endopeptidases but usually lack the hydrolase activity of the later. Butelase-1 and VyPAL2, two PALs discovered by NTU scientists, have been used successfully for peptide cyclization and C- or N-terminus-specific protein labelling as reported in a number of publications. However, as a new class of peptide ligases, the scope of their catalytic activity and application remains underexplored. Built upon previous findings by our teams in NTU and other groups from around the world, my thesis work aims to further understand the catalytic behaviours and explore the applications of these PAL enzymes for the development of protein- and cell-based therapeutics for disease treatment.